A Novel Strategy to Regulate 1-Deoxynojirimycin Production Based on Its Biosynthetic Pathway in Streptomyces lavendulae - Wu, Hao; Guo, Ye; Chen, Lei; Chen, Guiguang; Liang, Zhiqun (Frontiers in Microbiology, 2019)
This study characterized the biosynthetic pathway of the secondary metabolite 1-deoxynojirimycin (DNJ) from Streptomyces lavendulae. The results revealed that glucose was a preferable precursor for DNJ synthesis, and its carbon skeleton underwent a C2-N-C6 cyclization reaction during synthesis. The biosynthetic pathway was related to the glycolysis pathway, and started from fructose-6-phosphate, and involved amination, dephosphorylation, oxidation, cyclization, dehydration, and reduction reaction steps, yielding DNJ. Then, based on clarified biosynthetic pathway information, precursors, analogues, and metabolism inhibitors were used as novel regulators to enhance the production of DNJ. The results demonstrated that the titre of DNJ could reach 296.56 mg/L, which was 3.3-fold higher than that of a control group (90 mg/L) when sodium citrate (0 h, 5 g/L), sorbose (0 h, 1 g/L), iodoacetic acid (20 h, 50 mg/L), and glucose (26 h, 7 g/L) were added during the fermentation process. This study provides a new understanding of the biosynthetic pathway of DNJ, and also provides an efficient strategy to regulate the production of DNJ based on this biosynthetic pathway, which is a new perspective for the regulation of other secondary metabolites.